1995
DOI: 10.1073/pnas.92.26.12398
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional clearance of hepatitis B virus RNA by cytotoxic T lymphocyte-activated hepatocytes.

Abstract: Using transgenic mice that replicate the hepatitis B virus (HBV) genome, we recently demonstrated that class I-restricted, hepatitis B surface antigen-specific cytotoxic T lymphocytes (CTLs) can noncytolytically eliminate HBV pregenomic and envelope RNA transcripts from the hepatocyte. We now demonstrate that the steady-state content of these viral transcripts is profoundly reduced in the nucleus and cytoplasm of CTL-activated hepatocytes, but their transcription rates are only slightly reduced. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 35 publications
(19 reference statements)
3
72
0
2
Order By: Relevance
“…Along these lines, based on evidence from a transgenic mouse model, we have recently suggested that hepatitis B virus (HBV)-specific CTL may control HBV infection not only by killing infected hepatocytes but also by inhibiting HBV replication by secreting certain antiviral cytokines when they recognize antigen (30,31). If this or related potentially curative antiviral pathways are required for viral clearance to be complete in an organ with as many infectible cells as the liver, viruses that are either intrinsically resistant to noncytolytic control or that induce an immune response that does not produce the corresponding antiviral cytokines would have a survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, based on evidence from a transgenic mouse model, we have recently suggested that hepatitis B virus (HBV)-specific CTL may control HBV infection not only by killing infected hepatocytes but also by inhibiting HBV replication by secreting certain antiviral cytokines when they recognize antigen (30,31). If this or related potentially curative antiviral pathways are required for viral clearance to be complete in an organ with as many infectible cells as the liver, viruses that are either intrinsically resistant to noncytolytic control or that induce an immune response that does not produce the corresponding antiviral cytokines would have a survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, we know that the cytokines inhibit viral gene expression by a posttranscriptional mechanism that destabilizes the viral mRNA in the nucleus of the cell, 51 and we have shown that this is associated with the cytokine-induced proteolytic cleavage of a cellular HBV RNA-binding protein that stabilizes the viral RNA under baseline conditions. 52,53 We also know that the cytokines inhibit viral replication by posttranslationally eliminating viral nucleocapsid particles, within which replication occurs, from the cytoplasm of the hepatocyte (Wieland S, Guidotti LG, Chisari FV, J Virol, in press).…”
Section: Ctl-induced Viral Clearance In Hbv Transgenic Micementioning
confidence: 99%
“…Recently, however, we have shown that adoptively transferred hepatitis B surface antigen (HBsAg)-specific CTL can abolish HBV gene expression (2) and replication (3) in HBV transgenic mice by secreting interferon y (IFN-'y) and tumor necrosis factor a (TNF-a) after antigen recognition. Further, we have reported that these cytokines deliver two noncytopathic antiviral signals to the hepatocyte: one that activates the hepatocyte to degrade HBV RNA posttranscriptionally in a sequence-specific manner (4) and one that causes the hepatocytes to eliminate HBV nucleocapsid particles and their cargo of replicating viral genomes (3). It is possible, therefore, that these noncytopathic antiviral processes may exert an important but previously unsuspected influence on the outcome of HBV infection in man.…”
mentioning
confidence: 99%